2014
DOI: 10.1371/journal.pone.0083477
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the G1 - S transition Checkpoint on an Age Structured Cell Cycle Model

Abstract: Knowledge of how a population of cancerous cells progress through the cell cycle is vital if the population is to be treated effectively, as treatment outcome is dependent on the phase distributions of the population. Estimates on the phase distribution may be obtained experimentally however the errors present in these estimates may effect treatment efficacy and planning. If mathematical models are to be used to make accurate, quantitative predictions concerning treatments, whose efficacy is phase dependent, k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In all our simulations we observed that the derivative of the transition age is always smaller than one (Results not shown). To avoid restricting the parameter regime, age-structured models with multiple compartments for the cell-cycle phases [6,10] can be considered.…”
Section: Discussionmentioning
confidence: 99%
“…In all our simulations we observed that the derivative of the transition age is always smaller than one (Results not shown). To avoid restricting the parameter regime, age-structured models with multiple compartments for the cell-cycle phases [6,10] can be considered.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of different transition rate functions in cell-cycle PBMs has indicated that the particular function used had little impact on the ability of the model to fit the experimental data [27]. We assumed a normal cumulative distribution function for the transition probabilities G(C E ) and G(C B ) (see §1 in the electronic supplementary material).…”
Section: Development Of a Multi-stage Population Balance Model Based On Cyclin Concentrationmentioning
confidence: 99%
“…In this case, model parameters are activation and degradation rates of regulatory proteins and their concentration. Alternatively, the model can include expressions for the percentage of cells that are found to be in a given cell-cycle phase, thus providing a “population overview” 7 , 8 . Model parameters are then transition probabilities between different phases.…”
Section: Introductionmentioning
confidence: 99%